The Effects of Gender, Functional Condition, and ADL on Pressure Pain Threshold in Stroke Patients - Zhang, Yong-Hui; Wang, Yu-Chen; Hu, Gong-Wei; Ding, Xiao-Qin; Shen, Xiao-Hua; Yang, Hui; Rong, Ji-Feng; Wang, Xue-Qiang (Frontiers in Neuroscience, 2021)
Background. Somatosensory impairments and pain are common symptoms following stroke. However, it is still unclear the condition of perception and pain threshold for pressure stimuli and what factors can influence this in individuals with stroke. This study aimed to investigate the gender differences in pressure pain threshold (PPT) and positive somatosensory signs for pressure stimuli, and explore the effects of joint pain, motor function, and activities of daily living (ADL) on pain threshold in post-stroke patients. Design. A cross-sectional study. Methods. A total of 60 participants with stroke were recruited, and their pain condition, motor functions, and ADL were evaluated by Fugl-Meyer assessment of joint pain scale, motor function scale, and Barthel index, respectively. PPTs in eight tested points at the affected and unaffected sides were assessed. Results. Significant differences in PPTs were found between male and female patients in all measured muscles (p < 0.05). Positive somatosensory signs for pressure stimuli, including hypoalgesia and hyperalgesia, were frequently found at the affected side, particularly in extremity muscles, but such signs were not significantly influenced by gender (p > 0.05). More equal PPTs between both sides and lower relative PPTs at the affected side in trunk and medial gastrocnemius muscles (p < 0.05) were observed in patients with less pain, better motor functions, and ADL. Conclusions. Gender differences widely exist in post-stroke survivors either at the affected or unaffected side, which are multifactorial. Sensory loss and central and/or peripheral sensitization, such as hypoalgesia and hyperalgesia for pressure stimuli, caused by brain lesion are common signs in male and female stroke patients. Moreover, patients in better condition show more symmetrical pain sensitivity between both sides in trunk and female lower extremities, indicating the bidirectional improvement of somatosensory abnormalities caused by possible neural plasticity.